1997
DOI: 10.1097/00007435-199705000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium in the Cervices of Japanese Women

Abstract: A significantly greater prevalence of M. genitalium was demonstrated in Japanese women with Chlamydia-negative cervicitis or adnexitis, compared with that in asymptomatic pregnant women. This study suggests that M. genitalium may play a pathogenic role in a portion of cases with Chlamydia-negative genital infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 8 publications
5
66
1
6
Order By: Relevance
“…The low prevalence for M. genitalium in our study suggests that the cervix of healthy, fertile women is only rarely colonized with this organism. This is also in agreement with previous findings [Uno et al 1997]. Even though the number of samples examined in the present study was relatively low, cervical swabs from the women had high prevalence of both C. trachomatis and M. hominis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The low prevalence for M. genitalium in our study suggests that the cervix of healthy, fertile women is only rarely colonized with this organism. This is also in agreement with previous findings [Uno et al 1997]. Even though the number of samples examined in the present study was relatively low, cervical swabs from the women had high prevalence of both C. trachomatis and M. hominis.…”
Section: Discussionsupporting
confidence: 93%
“…None of the healthy controls in that study were carrying M. genitalium. The study by Uno et al [1997] analysed women suffering from urethritis and adnexitis and found 7.8% and 5.7%, respectively, of the patients were M. genitalium positive. In contrast, 80 pregnant asymptomatic women, also tested in that study, were all negative for M. genitalium DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Uno y cols detectaron a M. genitalium en 5 de 64 (7,8%) mujeres con cervicitis. Luego de la exclusión de las pacientes positivas para C. trachomatis, M. genitalium estuvo asociado con 5 de 57 (8,8%) casos 10 . Finalmente, Manhart y cols detectaron M. genitalium en 50 de 719 (7,0%) muestras cervicales de pacientes con cervicitis mucopurulenta atendidas en una clínica de Enfermedades de Transmisión Sexual (ETS) 11 .…”
Section: Discussionunclassified
“…Varios estudios efectuados mediante RPC han detectado M. genitalium en 15 a 25% de hombres con UNG [5][6][7][8][9] . En la mujer, M. genitalium ha sido asociado con cervicitis 5,[10][11] , enfermedad inflama-muestras clínicas fueron obtenidas con tórula fina de algodón e inmediatamente inoculadas en medio de transporte Stuart y en 1,5 ml de buffer de transporte sacarosa fosfato (buffer 2SP). Mujeres sexualmente activas: se obtuvieron dos muestras de secreción vaginal de 40 mujeres atendidas consecutivamente en el Departamento de Alto Riesgo Obstétrico (DARO) del Hospital San Juan de Dios.…”
Section: Materials Y Métodosunclassified
“…Despite the challenges facing the study of anaerobic PID, since only a third to a half of PID cases are attributed to N. gonorrhoeae and/or C. trachomatis, and because BV, anaerobic Gram-negative rods and mycoplasmal bacteria have been identified among women with PID [7][8][9][10]81], the microbiologic efficacy of PID treatment regimens for both chlamydial/gonococcal and nonchlamydial/nongonococcal PID should be determined. Over the next 5 years, several areas of study are likely to take center stage, focusing on the identification of novel pathogens associated with PID, so that existing regimens can be examined for microbiologic efficacy and new broad-spectrum regimens can be tested and proposed as needed.…”
Section: Future Perspectivementioning
confidence: 99%